2016
DOI: 10.1002/chem.201600167
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Synthesis of Polysubstituted Pyridines from Heteroaryl Fluorosulfates

Abstract: A selection of heteroaryl fluorosulfates were readily synthesized using commercial SO2F2 gas. These substrates are highly efficient coupling partners in the Suzuki reaction. Through judicious selection of Pd-catalysts, the fluorosulfate functionality is differentiated from bromide and chloride; the order of reactivity being: -Br > -OSO2F > -Cl. Exploiting this trend allowed the stepwise chemoselective synthesis of a number of polysubstituted pyridines, including the drug, Etoricoxib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 31 publications
5
44
0
1
Order By: Relevance
“…When the sulfurofluoridoimidate 6-6 itself was exposed to the aryl silyl ether ( 5-5 ) in the presence of DBU (10 mol%) over 16 h, SuFEx catalysis achieved linkage exchange at the fluorosulfate group, yielding the mixed sulfate-sulfurofluoridoimidate linked product 6-7 (Figure 7). From these few experiments, and related work, [7,15] we tentatively suggest the order of reactivity of SO 2 F 2 and SOF 4 derived S-F bonds towards SuFEx reactions with aryl silyl ethers: –N=SOF 2 > -SO 2 F > –OSO 2 F > –N=S(O)(OAr)F.…”
Section: Iminosulfur Oxydifluorides With Aryl Silyl Etherssupporting
confidence: 54%
See 2 more Smart Citations
“…When the sulfurofluoridoimidate 6-6 itself was exposed to the aryl silyl ether ( 5-5 ) in the presence of DBU (10 mol%) over 16 h, SuFEx catalysis achieved linkage exchange at the fluorosulfate group, yielding the mixed sulfate-sulfurofluoridoimidate linked product 6-7 (Figure 7). From these few experiments, and related work, [7,15] we tentatively suggest the order of reactivity of SO 2 F 2 and SOF 4 derived S-F bonds towards SuFEx reactions with aryl silyl ethers: –N=SOF 2 > -SO 2 F > –OSO 2 F > –N=S(O)(OAr)F.…”
Section: Iminosulfur Oxydifluorides With Aryl Silyl Etherssupporting
confidence: 54%
“…Under SuFEx conditions the latent reactivity of the otherwise stable S VI –F bond is roused to react with SuFExable substrates. [7,15] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated the effect of bases and co-solvents and found that, in the presence of 20 equivalents of Pd(OAc) 2 , 400 equivalents of boronic acid, and 1000 equivalents of triethylamine (Et 3 N) with N,N-dimethylaniline (DMA) as a co-solvent, the cross-coupling reaction proceeded smoothly with excellent conversion (90%) at room temperature in a ligand-free style (see Table S2, Supporting Information). [41,53] To further exploit the potential, it would be of great interest to perform stepwise chemo-selective on-DNA synthesis of polysubstituted aryl and/or heteroaryl molecules, [18] which are challenging tasks even in conventional organic synthesis. As shown in Scheme 1, the reaction displayed good reactivity and tolerance to aryl boronic acids with functional groups both electron-rich (KB1, KB2, KB3, KB4, KB16, KB19, and KB25) and electrondeficient (KB11, KB12, KB13, KB14, KB21, and KB24).…”
Section: Resultsmentioning
confidence: 99%
“…在 100 mL 的三颈烧瓶中加入 1.83 mmol 苯硼酸, 1.67 mmol 3-溴吡啶, 0.33 mmol NaHCO 3 作为碱, 0.002 g PdCl 2 作为催化剂, 溶剂为 30 mL 乙醇和水的混合溶液 [V(乙醇)∶V(水)=2∶1], 在 90 ℃下反应 25 min [32] .…”
Section: Suzuki 反应unclassified